Ω-3 and major depression: a review. Issue 3 (14th October 2013) - Mello, Aline H.; Gassenferth, Aline; Souza, Luana R.; Fortunato, Jucélia J.; Rezin, Gislaine T.
<x content-type="archive" xml:space="preserve">Abstract</x> Background The World Health Organization estimates that major depression affects about 350 million people all over the world and reports this disorder as the major contributor to the global burden of diseases. Despite the well-defined symptomatology, major depression is a heterogeneous psychiatric disorder whose pathophysiology is not clearly established. Although several treatments are available, most depressed patients do not achieve the complete remission of symptoms. Factors linked to the persistence of the disorder have been investigated, particularly those related to the way of life. Moreover, it has been suggested that nutritional aspects may influence its development. Among them, a diet rich in ω-3 has been associated with a reduced risk of major depression, although its deficiency is associated with depressive disorders. Methods This review provides a general view about evidences of the use of ω-3 in major depression cases. Results Several studies have demonstrated beneficial effects of ω-3 in the prevention and treatment of major depression. However, not all the results have shown significant statistical benefits. Conclusions More studies are necessary to clarify detailed mechanisms of the antidepressant effects of ω-3 and may explain the source of contradictions in results published until the moment.